2004
DOI: 10.1016/j.finel.2004.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Stabilized conforming nodal integration: exactness and variational justification

Abstract: In most Galerkin mesh-free methods, background integration cells partitioning the problem domain are required to evaluate the weak form. It is therefore worthwhile to consider these methods using the notions of domain decomposition with the integration cells being the subdomains. Presuming that the analytical solution is admissible in the trial solution, domain and boundary integration exactness, which depend on the orders of the employed trial solution and the required solution exactness, are identified for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…The smoothing technique proposed in [28] is one of the most efficient nodal integration methods available, and has been applied successfully to various analysis problems [9,10,[33][34][35]. In this technique nodal values are determined by spatially averaging field values using the divergence theorem.…”
Section: Introductionmentioning
confidence: 99%
“…The smoothing technique proposed in [28] is one of the most efficient nodal integration methods available, and has been applied successfully to various analysis problems [9,10,[33][34][35]. In this technique nodal values are determined by spatially averaging field values using the divergence theorem.…”
Section: Introductionmentioning
confidence: 99%
“…The strain smoothing method was then modified to allow stabilization in nodal integration schemes, leading to the so-called stabilized conforming nodal integration (SCNI) scheme [11]. The SCNI scheme was then successfully applied to both elastic analysis [12,13] and plastic analysis [9] problems. It has been shown that the SCNI scheme results in an efficient and truly mesh-free method, and also to numerically stable solutions.…”
Section: Stabilized Equilibrium Equationmentioning
confidence: 99%
“…The main idea of the scheme is that nodal values are determined by spatially averaging field values using the divergence theorem. The scheme has been applied successfully to various analysis problems [9,[12][13][14]. It is shown that, when the SCNI scheme is applied, the solutions obtained are accurate and stable, and the computational cost is much lower than when using Gauss integration.…”
Section: Introductionmentioning
confidence: 99%
“…It is known as the stabilized conforming nodal integration (SCNI) scheme. The SCNI scheme has been applied successfully to various problems, for instance, elastic analysis [12][13][14], plastic limit analysis [15], error estimation [16] and a stabilized mesh-free equilibrium model for limit analysis [17]. It is shown that, when the SCNI scheme is applied, the solutions obtained are accurate and stable, and locking problems can also be prevented.…”
Section: Introductionmentioning
confidence: 99%